Influence of Microalloying Element on the Microstructure and Mechanical Properties of 34CrNiMo6 Steel for Wind Turbine Main Shaft - Yanming Ge; Kehong Wang (Advances in Materials Science and Engineering)
The influence of the microalloying elements of 34CrNiMo6 steel on the microstructure and mechanical properties is investigated in this paper, especially Al and N. Then, the testing of the tensile strength, yield strength, elongation after breakage, and impact absorbing energy under the different conditions is carried out to compare the mechanical properties of materials. Based on the experimental results, the evolutions of mechanical properties with the content of aluminum are obtained. The average grain size test and scanning electron microscope results illustrate that the strengthening mechanism is the pinning effect of aluminum nitride.